Modern approaches to physical therapy of women with diastasis recti of the abdominal muscles as a result of multiple pregnancy - Bezuhla, Mariia; Yudenko, Oksana (The Ukrainian Scientific Medical Youth Journal, 2023)
It is a well-known fact that the development of diastasis of the rectus muscles with the progression of pregnancy is considered a natural and practically physiological phenomenon. World information sources indicate that in the last trimester, diastasis of the rectus muscles is recorded in 66-100% of all pregnancies in women. An increase in the volume of the pregnant uterus leads to an increase in intra-abdominal pressure and stretches the anterior abdominal wall. The development of diastasis is facilitated by a decrease in the strength of connective tissue collagen, which occurs as a result of physiological changes in the body of a pregnant woman. During pregnancy, the production of the hormone relaxin, whose biological function is to inhibit collagen synthesis and stimulate its breakdown, increases dramatically. The purpose of the study is to determine the effectiveness of the author’s physical therapy programme for women with diastasis of the rectus abdominis muscles due to multiple pregnancy and to characterise the diagnostic tools used in the study. Based on the analysis of information sources, effective innovative means of physical therapy for pregnant women with diastasis of the rectus abdominis due to multiple pregnancy were identified. They include (special therapeutic exercises for the indicated dysfunction (diastasis recti); post-isometric relaxation exercises; exercises from the Body&Mind Fitness system such as yoga therapy and elements of the Pilates system; hydroki- nesitherapy and kinesotaping; therapeutic massage and electro-myostimulation). The diagnostic card included such methods of determining such indicators as your pain at rest; determination of cortical muscle tone during movements and palpation using the Lovett manual muscle test; the Pelvic Floor Impact Questionnaire – Short Form 7 (PFIQ-7) was used; the Hospital Anxiety and Depression Scale, SAN, PHQ-9, and Quality of Life were used to determine the psycho-emotional state; and mathemat- ical statistics methods were applied. The paper presents the results of the study obtained during the work with 20 women in labour, on the basis of which the authors draw conclusions about the effec- tiveness of the developed and implemented author’s physical therapy programme. However, realising that the study used a small sample of patients in the main group with the above-mentioned pregnancy characteristics, we continued to work with this contingent and further implement the author’s pro- gramme of physical therapy for parturients with diastasis of the rectus abdominis muscles due to multiple pregnancies. In the course of solving the tasks of the work, the effectiveness of individual and integrated approaches in the construction of individual physical therapy programmes for women withthese dysfunctions due to pregnancy has been proven to significantly improve and contribute to a more complete and qualitative restoration of the functional capabilities of the musculoskeletal system of women with diastasis recti.